Agama, Etnisitas dan Perdamaian di Pulau Enggano Provinsi Bengkulu - Sari, Intan Permata (Hanifiya: Jurnal Studi Agama-Agama, 2020)
This article explores the diversity of ethnicities and religions in the Engganese society, which has become color in their life dynamics—local wisdom based on customary rules succeeded in uniting differences into peace. Ethnic and religious differences, which have been considered dividing the nation, did not occur in the Enggano community. This study uses a qualitative method by interviewing several vital informants who are religious or traditional leaders. The purpose of this study is to show that ethnic and religious differences can create harmony and peace in society. The results of this study are that the Enggano community is an open society that easily accepts the presence of newcomers; then that migrants get the same rights and obligations as indigenous people; also that migrants are required to give up their cultural identity when entering Enggano; that religion is a new value in the Enggano community which is not regulated by custom; and that adat has an important role in shaping the behavior of the Engganese people. These factors are the keys to peace in a multi-ethnic and multi-religious society.